Biogenic volatile release from permafrost thaw is determined by the soil microbial sink - Magnus Kramshøj (Nature Portfolio, 2018)
Permafrost thaw allows biological activity in previously frozen ground, leading to a potential release of climate-relevant gases. Here the authors show that thawing permafrost emits volatile organic compounds but that their release to the atmosphere is limited by microbial consumption in the overlaying soil.